PRESENTEEISM AND ORGANIZATIONAL PERFORMANCE OF GOVERNMENT PARASTATALS IN PORT HARCOURT, RIVERS STATE - Okpara Benjamin Chekwube; Felix O. Oloda (PhD) (Journal Park Publishing, 2025)
This study examined the relationship between Presenteeism and Organizational Performance of Government Parastatals in Port Harcourt, Rivers State. The study adopted the quasi-experimental research design, and data were collected from 226 employees across selected government parastatals using questionnaire. The spearman rank order Correlation Coefficient statistical tool was employed to test the hypotheses. Findings from this study revealed weak and none significant relationships between the two dimensions of presenteeism (sickness presenteeism and non-work related presenteeism) and the two measures of organizational performance (service quality and productivity). The study recommends that measures be put in a place to ensure that workers conform to the rules and regulations guiding the establishment in their workplace. There should be Policy Overhaul which ensures that line managers understand the relationship between absenteeism and presenteeism, that they are supported to adopt a more flexible approach to absence, and that they provide support to employees making a return to work after a period of illness. Managers should be able to recognize the symptoms of non-work related presenteeism, this implies that workplace training and awareness raising of common mental and physical health issues will help reduce stigma and provide people with a better understanding of workplace wellbeing which can in turn enhance service quality.
Keywords: presenteeism, organizational performance, productivity, service quality, absenteeism.